Iterative scheme for a nonexpansive mapping, an _-strictly pseudo-contractive mapping and variational inequality problems in a uniformly convex and 2-uniformly smooth Banach space - Atid Kangtunyakarn (My University, 2013)
In this paper, we introduce an iterative scheme by the modification of Mann’s iteration process for finding a common element of the set of solutions of a finite family of variational inequality problems and the set of fixed points of an η-strictly pseudo-contractive mapping and a nonexpansive mapping. Moreover, we prove a strong convergence theorem for finding a common element of the set of fixed points of a finite family of -strictly pseudo-contractive mappings for every in uniformly convex and 2-uniformly smooth Banach spaces.
Keywords: Uniformly convex space; Optimization and Variational Analysis